Designing Predictive Controller Based on Nonlinear Model for Multi-Stage Med Desalination Systems - Soleymanizadeh, Ali; Shayanfar, Heidar Ali (Ciência e Natura, 2015)
Due to the use of fossil energy and environmentally pollutant fuels, groundwater and surface water pollution has led to a more progressive movement towards the technology of desalination systems in recent decades so that the issue of the desalination of seawaters and ocean waters has received great attention from most countries. In the meantime, the use of distillation desalination systems has been welcomed more than other systems because they take advantage of the sun’s energy and do not negatively influence the environment. The PDE and nonlinear model of multi-effect desalination systems constitutes the structure under study in this paper. In order to control the variables of this model, a nonlinear predictive model controller (NPMC) has been proposed. The results obtained from the conduct of this controller on multi-effect desalination system in MATLAB Software is indicative of the acceptable performance of the controller.